EXPERIENCE IN USING A HYGIENE PRODUCT CONTAINING MODIFIED SORBENTS FOR EROSIVE AND ULCERATIVE-NECROTIC SKIN LESIONS - N. V. Shperling; N. N. Svechnikova; I. A. Shperling; M. A. Korolev; L. N. Rachkovskaya; A. A. Kotlyarova; T. V. Popova; A. Yu. Letyagin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
In this study, we have evaluated clinical efficacy of the topical universal hygiene product ‘Bodyguard’ containing porous silicon-containing sorbent with microdoses of silver and lithium for the treatment of primary erosive or secondary ulcerative-necrotic skin lesions. We used this product in a female patient with lipoid necrobiosis of the skin: necrotic smell disappeared 2 days after sorbent application; the amount of discharge decreased after 4 days; granulations developed after 14 days; scarring continued for the next 3 weeks. In a patient with erosive lesions on the face after chemical peeling, ‘Bodyguard’ reduced pain and swelling and ensured complete epithelization of the damaged area without scarring and pigmentation after 14 days. In a patient with postoperative subcutaneous hematoma, the sorbent stopped ulcerative-necrotic skin lesions within 21 days, eliminated edema and pain, optimized healing, and prevented pathological scarring; the patient demonstrated complete epithelization in the area of skin defect 3 months later. Positive effects of the sorbent ‘Bodyguard’ are associated with its sorption properties (neutralization of products of free radical reactions and products of tissue alteration) and with the antibacterial effect of silver, which provides analgesic, anti-inflammatory, dehydrating (drying), cleansing, and wound healing effects.